2021
DOI: 10.1021/acsenergylett.1c01018
|View full text |Cite
|
Sign up to set email alerts
|

Toward Stable Monolithic Perovskite/Silicon Tandem Photovoltaics: A Six-Month Outdoor Performance Study in a Hot and Humid Climate

Abstract: Perovskite/silicon tandem solar cells are emerging as a highefficiency and prospectively cost-effective solar technology with great promise for deployment at the utility scale. However, despite the remarkable performance progress reported lately, assuring sufficient device stabilityparticularly of the perovskite top cellremains a challenge on the path to practical impact. In this work, we analyze the outdoor performance of encapsulated bifacial perovskite/silicon tandems, by carrying out field-testing in Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 40 publications
0
51
0
Order By: Relevance
“…[214] Ag oxidation was observed at both the front and rear sides of the textured monolithic perovskite-SHJ tandem solar cell after 250 h of stability testing (glass/ glass with edge sealant but no encapsulant, Figure 6a) and after 6 months in the field. [75,192] The Ag oxidation on the rear side of the tandem cell suggests that some iodide transport may have occurred in the form of volatile species during operation. Alternatively, metals may also diffuse into the absorber during operation and degrade it (Figure 6a).…”
Section: Metal Electrode Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…[214] Ag oxidation was observed at both the front and rear sides of the textured monolithic perovskite-SHJ tandem solar cell after 250 h of stability testing (glass/ glass with edge sealant but no encapsulant, Figure 6a) and after 6 months in the field. [75,192] The Ag oxidation on the rear side of the tandem cell suggests that some iodide transport may have occurred in the form of volatile species during operation. Alternatively, metals may also diffuse into the absorber during operation and degrade it (Figure 6a).…”
Section: Metal Electrode Degradationmentioning
confidence: 99%
“…And similarly to light and elevated temperature-induced degradation occurring in PERC cells, [231,232] operations in the field of the first perovskite(-silicon) tandem modules will certainly reveal additional degradation pathways not anticipated in the laboratory. [233,234] 6. Other Monolithic Tandem Cell Designs…”
Section: Other Field Operation Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[136][137][138][139][140][141][142][143][144] For chemical stability, the encapsulation of PSK devices can effectively improve the tolerance to moisture and oxygen and avoid the causative factor of PSK crystal dissociation. [145][146][147][148][149][150] However, it has been an insurmountable problem for physical stability, because the lattice of PSK is not stable, temperature alone can induce phase changes, 151,152 and ion diffusion and migration occur all the time (e.g., the activation energy of I À for vacancy-assisted migration is only 0.6 eV 133 ). Moreover, several studies 138,143 have shown that ion migration may be one of the causes of lightinduced phase segregation in wide-bandgap mixed halide PSK, indicating that the physical dissociation factors are not independent but complementary.…”
Section: Stability Issuesmentioning
confidence: 99%
“…136–144 For chemical stability, the encapsulation of PSK devices can effectively improve the tolerance to moisture and oxygen and avoid the causative factor of PSK crystal dissociation. 145–150 However, it has been an insurmountable problem for physical stability, because the lattice of PSK is not stable, temperature alone can induce phase changes, 151,152 and ion diffusion and migration occur all the time ( e.g. , the activation energy of I − for vacancy-assisted migration is only 0.6 eV 133 ).…”
Section: Metrics For Practical Applications Of the Psk/c-si Tscmentioning
confidence: 99%